Propuesta de Plan estratégico para el Desarrollo y Aprovechamiento del Sistema de Gestión Integral en DEQUISA S.A. (2017-2021) - Segura-Romero, Deivid Stiven (Instituto Tecnológico de Costa Rica, 2017)
This work establishes a Strategic Plan with a scope of five years, for the company DEQUISA, which is an organization belonging to the Outsourcing market in Professional Cleaning Services, which has more than 30 years of operation, being the pioneer organization and one of the most representative of this sector. Although, this company has important strengths such as its brand positioning and recognition of the quality of its services, it also has problems arising from changes in market demands and the growth of competition, causing the organization to make great efforts to achieve certifications in good practices and improve their administrative processes. Given the above, this Strategic Plan aimed to establish a guide for DEQUISA to direct its efforts to the fulfillment of its goals in the short, medium and long term, by knowing its situation both in its internal and external variables, development Of objectives and the establishment of strategic initiatives that outline the path to take in order to achieve its objectives. This made it possible to identify the importance of the successful implementation of the Integral Management System being developed by the organization to obtain the relevant certifications and the need to extend its position in the private sector to improve its profitability and sustainability. Therefore, this proposal is the product of an in-depth analysis of the variables that influence internally and externally in the achievement of its goals and its association with the modern theories of Strategic Management, for which, it represents a tool of great impact and utility for the Organization in its processes of continuous improvement and business growth.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2017.
Keywords: Plan; Estrategia; Sistema de gestión integral; Limpieza profesional; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies